Divergent regulation of auxin responsive genes in root-knot and cyst nematodes feeding sites formed in Arabidopsis - Abril-Urias, Patricia; Ruiz-Ferrer, Virginia; Cabrera, Javier; Olmo, Rocio; Silva, Ana Cláudia; Díaz-Manzano, Fernando Evaristo; Domínguez-Figueroa, Jose; Martínez-Gómez, Ángela; Gómez-Rojas, Almudena; Moreno-Risueno, Miguel Ángel; Fenoll, Carmen; Escobar, Carolina (Frontiers in Plant Science, 2023)
Cyst (CNs) and root-knot nematodes (RKNs) induce specialized feeding cells, syncytia and giant cells (GCs), respectively, within plant roots. The plant tissues around the GCs usually respond forming a root swelling called gall that contains the GCs. The ontogenesis of the feeding cells is different. GCs formation is a process of new organogenesis from vascular cells still not well characterized, that differentiate into GCs. In contrast, syncytia formation involves the fusion of adjacent cells already differentiated. Nonetheless, both feeding sites show an auxin maximum pertinent for feeding site formation. However, data on the molecular divergences and similarities between the formation of both feeding sites regarding auxin responsive genes is still scarce. We studied genes from the auxin transduction pathways that are crucial during gall and lateral root (LR) development, in the CNs interaction. The promoters pGATA23 and several deletions of the pmiR390a were active in syncytia, as were in galls, but pAHP6 or putative up-stream regulators as ARF5/7/19 were not active in syncytia. Additionally, none of these genes seemed to play a key role during cyst nematodes establishment in Arabidopsis, as the infection rates in loss of function lines did not show significant differences compared to control Col-0 plants. Furthermore, the presence of only canonical AuxRe elements in their proximal promoter regions highly correlated with their activation in galls/GCs (AHP6, LBD16), but those promoters active in syncytia (miR390, GATA23) carry AuxRe overlapping core cis-elements for other transcriptions factor families (i.e, bHLH, bZIP). Strikingly, in silico transcriptomic analysis showed very few genes up-regulated by auxins common to those induced in GCs and syncytia, despite the high number of up-regulated IAA responsive genes in both nematode feeding sites. The complex regulation of auxin transduction pathways, where different members of the auxin response factors (ARFs) family may interplay with other factors, the differences in auxin sensitivity, as indicated by the lower induction of the DR5 sensor in early developing syncytia than in galls, among other factors, may explain the divergent regulation of auxin responsive genes in the two types of nematode feeding sites.